Performance of Growing Sirohi Goats on Azolla (Azolla Pinnata) Based Diet - Dev, Rishabh; Nanavati, Sandeep; Jamra, Mohabbat S.; Patil, Ashok K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study assessed the effect of replacing concentrate mixture with sun-dried Azolla on voluntary feed intake and growth  performance in Sirohi goats. Twelve male Sirohi growing goat kids of 6 to 9 months of age with uniform body weight were divided into  two groups, control, and treatment, consisting of six animals in each group. The animals kept in group T1 were allowed to browse on  jungle grasses with 200 g concentrate mixture per day per animal, whereas in group T2, 10 % of the concentrate mixture was replaced  with sun-dried azolla. Weekly feed intake and body weights were recorded to assess the growth rate of goats. Results revealed that goats’  average weekly feed intake and body weight were comparable and statistically similar in both groups. The average daily gain (g) in the  bodyweight of a control group (51.79) and experimental group (65.60) was statistically similar but numerically higher in the treatment  group. In conclusion, supplementation of sun-dried azolla meal improved the performance of Sirohi goat without any detrimental  effect on voluntary feed intake and health.
Keywords: Azolla meal; Browsing; Concentrate; Growth performance; Sirohi goats